TRAF6 promotes TGFβ-induced invasion and cell-cycle regulation via Lys63-linked polyubiquitination of Lys178 in TGFβ type I receptor - Sundar, Reshma (Cell Cycle, 2015)
Transforming growth factor β (TGFβ) can act either as a tumor promoter or a tumor suppressor in a context-dependent manner. High levels of TGFβ are found in prostate cancer tissues and correlate with poor patient prognosis. We recently identified a novel TGFβ-regulated signaling cascade in which TGFβ type I receptor (TβRI) is activated by the E3 ligase TNF-receptor-associated factor 6 (TRAF6) via the Lys63-linked polyubiquitination of TβRI. TRAF6 also contributes to activation of TNF-α-converting enzyme and presenilin-1, resulting in the proteolytic cleavage of TβRI and releasing the intracellular domain of TβRI, which is translocated to the nucleus to promote tumor invasiveness. In this report, we provide evidence that Lys178 of TβRI is polyubiquitinated by TRAF6. Moreover, our data suggest that TRAF6-mediated Lys63-linked ubiquitination of the TβRI intracellular domain is a prerequisite for TGFβ regulation of mRNA for cyclin D1 (CCND1), expression, as well as for the regulation of other genes controlling the cell cycle, differentiation, and invasiveness of prostate cancer cells.